ENGLISH LEARNING GOALS AND WILLINGNESS TO COMMUNICATE: A QUALITATIVE ANALYSIS IN A JAPANESE EFL CONTEXT - Fujii, Satomi (TEFLIN Journal, 2023)
This study examined the differences in English learning goals and specific actions for goal achievement according to the degree of willingness to communicate (WTC) among Japanese English as a Foreign Language (EFL) learners through qualitative analysis. This study aimed to ascertain: 1) the characteristics of English learning goals among learners with higher or lower levels of WTC, and 2) the differences in learner actions for goal achievement among learners with higher or lower levels of WTC. The participants were 84 undergraduate students in Japan, and they were divided into high-WTC and low-WTC groups using the WTC scale (Peng & Woodrow, 2010). Open-ended responses of the goals for learning English and actions for goal achievement were compared between these two groups using KH Coder 3. Coded data were analyzed in a co-occurrence network diagram. Results showed that high-WTC learners tended to have high-level goals, whereas low-WTC learners tended to have the lowest possible goals. High-WTC learners also had more interest in foreign countries and studying abroad. Furthermore, high-WTC learners tended to take a variety of specific actions for goal achievement, while low-WTC learners took rather general and common actions. The results showed clear differences between these two groups.